TRACER DIFFUSION OF STAR-BRANCHED POLYSTYRENES IN POLY(VINYL METHYL-ETHER) GELS - WON, J; LODGE, TP (WILEY-BLACKWELL, 1993)
The tracer diffusion of 3-, 4-, and 12-arm polystyrene (PS) stars in poly(vinyl methyl ether) (PVME) gels has been measured by dynamic light scattering (DLS). The intensity correlation functions were analyzed by two methods. One was that employed previously in a DLS study of linear PS diffusion in PVME gels [N. A. Rotstein and T. P. Lodge, Macromolecules, Vol. 24, p. 1316 (1992)], and the other was based on consideration of possible nonergodicity effects [P. N. Pusey and W. van Megen, Physica A, Vol. 157, p. 705 (1990)]. Both methods gave equivalent results, suggesting that nonergodicity plays a small role in this system. This conclusion is not unreasonable, given that the PVME gels are almost isorefractive with the solvent (toluene), and that the signal is dominated by scattering from the PS chains. The resulting star diffusivities are consistently less than or equal to those for linear probes of comparable size, with the difference increasing with molecular weight. The diffusivities are also less than or equal to those obtained for the same stars in PVME solutions. A weak dependence on the number of arms is also observed. Finally, the mobility of a given star in a gel is much more sensitive to variations in the average molecular weight between cross-links than is the mobility of a linear chain. All of these features in the data are broadly consistent with the reptation hypothesis. (C) 1993 John Wiley & Sons, Inc.
Keywords: DYNAMIC LIGHT-SCATTERING; SEMIDILUTE POLYMER-SOLUTIONS; POLYVINYL METHYL-ETHER) SOLUTIONS; SELF-DIFFUSION; LINEAR POLYSTYRENES; POLYACRYLAMIDE GELS; COLLOIDAL PARTICLES; POROUS-MEDIA; MACROMOLECULES; BEHAVIOR